IMF Survey, Volume 32, Issue 01. (IMF Survey; IMF Survey ;, 2003)
IMF Managing Director Horst Kohler has recommended for Executive Board approval a transitional program for Argentina. The IMF said that while providing no net new financing, the arrangement would provide financial support and an extension of payment expectations to the IMF through August 2003. The Executive Board is expected to review the transitional program in the coming days.